Evaluation the performance efficiency of the Public Manufacturing Sector in Iraq for the Period (2000-2009) - هاشم سعاد قاسم; محمود محمد حسين (Journal of Economics and Administrative Sciences, 2014)
The industrial production sector has an important role in the national economy of the advanced countries as well as the developing ones to get higher levels for their economy . We in Iraq , just like most of the develpoing countries , our economy still suffers of great shortage in this active sector in spite of the repeated statements about the desire of activating the contribution of this sector in the national economy . The industrial sector in Iraq suffers in general of many problems , especially the public industrial sector (manufacturing) . These problems have been existed because of the unnatural conditions that Iraq has passed during the previous decades especially in the political and security sides . which reflected negatively on all sectors of the economy including the public industrial sector . The other factor is the policy followed by the administrative and economical parties in charge of this sector that have been responsible of depriving this sector of working in a competitive atmosphere . This situation has become worse after 2003 because of the illogical procedures used by economical managements with manufacturing sector in Iraq . This weakens the activity of these industries and weakens their production and adds to their inability to compete in the local market . We attempt through this research to answer the following question " Can the public industrial sector manage the sector of industry in Iraq as a leading sector?" . The objective of the study is showing the reality of the manufacturing in the public industrial sector in Iraq for the period (2000-2009) concentrating on the period after 2003 . We conclude that there is a necessity to give the private sector the chance to enter as a partner in managing and financing the manufacturing in the public industrial sector in Iraq in a graduate way . This has an importance in rising the efficiency of the performance of industrial companies and increasing their productivity. In addition to that, decreasing the financial burdens on the government, and ending most of the problems that the economical companies face . The most important problems are the weakness of Administration and corruption.